Små ingrepp med stora steg mot förändring - From Björk, Madelaine; Lindqvist, Jenny (2014)
Durban, South Africa’s third-largest city is a socially segregated post apartheid society, struggling with high unemployment and AIDS. The city becomes even more complex with a changing climate, creating an influx of people to the city, putting scarce resources under further stress. Warwick Junction, an important transport hub in the centre of Durban, holds a large site of informal trading alongside the formal markets. This informal sector generates large financial flows and provides for a rapidly growing population. The aim of this thesis is to develop an approach that is realistic and relevant to planning and design of an urban context in South Africa. The starting point is to support local activities and processes, and in the framework of what is possible through design of the physical environment, improve people’s living conditions. This is done in the form of a thesis that includes a proposal for a competition, where such an approach is requested. It raises the questions; How can we plan and design the physical environment in a city like Durban, where segregation, lack of resources and climate challenges are limitations? How can we plan and design the physical environment so that it supports a development that benefits disadvantaged people and the local community? The student competition organized by International Union of Architects (UIA) was used as a tool to reach the aim of the thesis. The student competition was located to Warwick Junction, where the contestants were to prepare a proposal in three scales that illustrates the development of the area. To understand the conditions and requirements of the site, we translated and interpreted the competition programs. Our interpretation of the competition’s conceptual themes directed the work throughout the thesis. These themes, related to the needs and requirements of the site, were emphasized in the conducted interviews, in the literature study as well as in the design proposal. In addition, an inventory and analysis of Warwick Junction was made. A concept and program originating from this, composed a ground for the design proposal. We found examples of extensive unsuccessful projects and that local rootedness is essential in development projects. The proposal therefore focuses on the ability of small interventions, which with time and civic engagement will drive the development process and eventually cause major changes without significant economic risks, giving people the tools and influence to generate the development at their own pace. To illustrate this development strategy, the short term - small scale intervention is presented first, followed by the medium term - medium scale intervention and long term – large scale intervention. With the world’s heavily exploited and dwindling resources, a landscape architect approach should strive to explore experimentally how the city’s resources can be used and produced to strive towards resilience.